2011
DOI: 10.1182/blood-2011-06-334672
|View full text |Cite
|
Sign up to set email alerts
|

The role of the annexin A2 heterotetramer in vascular fibrinolysis

Abstract: The vascular endothelial cells line the inner surface of blood vessels and function to maintain blood fluidity by producing the protease plasmin that removes blood clots from the vasculature, a process called fibrinolysis. Plasminogen receptors play a central role in the regulation of plasmin activity. The protein complex annexin A2 heterotetramer (AIIt) is an important plasminogen receptor at the surface of the endothelial cell. AIIt is composed of 2 molecules of annexin A2 (ANXA2) bound together by a dimer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
130
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(132 citation statements)
references
References 113 publications
(159 reference statements)
2
130
0
Order By: Relevance
“…Binding sites of the S100A10 proteins and t-PA have been identified in the N-terminal domain of annexin A2 at the amino acids residues 1-14 and 8-13, respectively (Kube et al 1992, Cesarman et al 1994. Recent data suggest that annexin A2 does not bind plasminogen directly but rather acts to transport S100A10 to the cell surface (Madureira et al 2011, Bydoun & Waisman 2014. Our findings suggest that the extracellular form of annexin A2 found in the cancer-associated stroma in the ovarian cancer tissues may represent a cleaved and secreted form of annexin A2, which may assist in ovarian cancer progression and metastasis.…”
Section: :11mentioning
confidence: 70%
“…Binding sites of the S100A10 proteins and t-PA have been identified in the N-terminal domain of annexin A2 at the amino acids residues 1-14 and 8-13, respectively (Kube et al 1992, Cesarman et al 1994. Recent data suggest that annexin A2 does not bind plasminogen directly but rather acts to transport S100A10 to the cell surface (Madureira et al 2011, Bydoun & Waisman 2014. Our findings suggest that the extracellular form of annexin A2 found in the cancer-associated stroma in the ovarian cancer tissues may represent a cleaved and secreted form of annexin A2, which may assist in ovarian cancer progression and metastasis.…”
Section: :11mentioning
confidence: 70%
“…These interactions are optimised by binding of the key proteins to relevant surfaces, either the surface of a fibrin clot or the surface of endothelial cells lining the blood vessel [26]. Recent research has identified the annexin A2 heterotetramer (AIIt), comprising two molecules of annexin A2 and two of the protein S100A10, as the key endothelial receptor bringing together both plasminogen and tPA to optimise plasmin generation at the surface of the vascular wall [27]. Annexin A2 binds to anionic phospholipids, chiefly phosphatidylserine (PS) [28], and thus anchors the S100A10 subunits to the membrane, where they act to co-localise plasminogen and tPA.…”
Section: Discussionmentioning
confidence: 99%
“…AXIIR gene encodes a protein with 193 amino acids which is only detected in primate species up to now [4]. As a member of the Annexins family, Annexin II involves in many cell functions such as endocytic and exocytotic vesicular transport, interaction with cell adhesion molecules, regulation of ion channels, and being receptor for tenascin-C and plasminogen [5,6,7]. Since AXIIR is originally identified as a receptor for Annexin II, several studies have investigated the role of AXIIR in mediating Annexin II signal.…”
Section: Introductionmentioning
confidence: 99%